2011
DOI: 10.1002/lsm.21066
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical tissue bonding: A potential strategy for treating limbal stem cell deficiency

Abstract: Bonding LSC grafts with PTB produced improved outcomes compared to suture attachment. This light-activated method is a promising modality for treating patients with LSCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…RB (4,5,6,7-tetrachloro-2=,4=,5=,7=-tetraiodofluorescein) is a deeply colored pink compound with a variety of medical uses. It is used as a stain to identify corneal damage (10), in the diagnosis of brucellosis (11), and as a PS to mediate photochemical tissue bonding (12). It has also been used as an anticancer compound (in the dark) given as an intralesional injection into transit melanoma metastases, where it has been shown to activate an antitumor immune response (13).…”
mentioning
confidence: 99%
“…RB (4,5,6,7-tetrachloro-2=,4=,5=,7=-tetraiodofluorescein) is a deeply colored pink compound with a variety of medical uses. It is used as a stain to identify corneal damage (10), in the diagnosis of brucellosis (11), and as a PS to mediate photochemical tissue bonding (12). It has also been used as an anticancer compound (in the dark) given as an intralesional injection into transit melanoma metastases, where it has been shown to activate an antitumor immune response (13).…”
mentioning
confidence: 99%
“…We have previously demonstrated that this technology can be used to seal wounds in cornea, to bond amniotic membrane to the corneal surface, and for applications in many other tissues. [16][17][18][19][20][21] In this study, we investigated whether photochemical cross-linking of cornea stromal collagen using RB and green light, a process called RGX, increases corneal stiffness. We investigated the processes involved and factors important for clinical application.…”
mentioning
confidence: 99%
“…This pink xanthene dye is used for the diagnosis of damage in corneal ( Doughty, 2013 ), brucellosis ( Ducrotoy and Bardosh, 2017 ). Rose Bengal in combination with the green light has been extensively studied with respect to photochemical tissue bonding and corneal transplants ( Gu et al, 2011 ; Gallego-Munoz et al, 2017 ). This compound was also studied in anti-tumor immune responses in melanoma models ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…RB possess a strong absorption band at 550 nm, and strong molar absorption coefficient (95,000 dm 3 mol −1 cm −1 ) ( Ludvikova et al, 2016 ). RB properties have been extensively investigated in technology known as photochemical tissue bonding in tissue repair ( Gu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%